Jahrbuch für die Geschichte des Protestantismus in Österreich 137 (2021) - Vorstand der Gesellschaft für die Geschichte des Protestantismus in Österreich (Evangelische Verlagsanstalt, 2022)
[Yearbook for the History of Protestantism in Austria 137 (2021)] The 137th volume of the Yearbook of the Society for the History of Protestantism will be published in 2021. It contains obituaries about deceased honorary members and an article about church politics in the era of the Minister of Culture Leo Thun 1849-1860. It documents a symposium in Eisenstadt about the theologian and interior designer Erwin Eugen Schneider. Two contributions are devoted to contemporary ecclesiastical history: the 100th anniversary of the province of Burgenland and the history of the Protestant Student Community in Austria. Two bibliographical contributions deal with the territorial history of Protestantism in Upper Austria and Lower Austria. Seven reviews of relevant publications round out the yearbook.